Opinion, perception and attitude of medical students towards family adoption programme- a cross sectional study - Gurav, Ravindra Balaram; Nair, Aishwarya Suresh; Tomar, Poornima (International Journal Of Community Medicine And Public Health, 2024)
Background: Right from first MBBS to third MBBS part one, the community medicine curriculum includes family adoption programme (FAP). It involves adopting families by medical students from underserved communities and tackling various health problems among them. Methods: This cross-sectional study was conducted among 232 MBBS students of Rajiv Gandhi Medical College, Thane in the month of January 2024 using purposive sampling method. Pre-designed proforma was used to record age and gender of the students and 18 Likert scale questions for assessing their opinion, perception and attitude towards FAP. The data was entered in Microsoft Excel and analysed. SE (p1-p2) test was applied. The statistical level of significance was fixed at p<0.05. Results: 150 (64.66%) students had strongly agreed for ‘FAP is important to understand the health problems among the adopted family’ and 112 (48.28%) to ‘FAP is essential to understand social problems among the adopted family’.76 (32.76%) subjects had strongly agreed for ‘FAP is useful to understand concept and structure of the family’ and 102 (43.97%) for ‘FAP is innovative way for learning community medicine’. 31 (13.36%) students had strongly agreed for ‘FAP should be conducted in urban area’ while 95 (40.95%) were for ‘FAP should be conducted in rural area’. 86 (37.07%) subjects had strongly agreed to ‘I am happy with the allotted families’. 95 (40.95%) students had strongly agreed for ‘FAP is the foundation of my future medical practice’. Conclusions: The medical students were highly motivated and under appropriate supervision they can create significant difference in promotion of health of the adopted families.